Accreditation of surgery residency training programs in a state teaching hospital: preparedness, areas of strengths and weaknesses - Iroegbu-Emeruem, Linda U.; Ijah, Rex Friday Ogoronte A.; Hart, Idawarifagha; Aaron, Friday E.; Aria, Oti N.; Achor, Mike T.; Danagogo, Okigboye (International Surgery Journal, 2025)
Background: Quality assurance is a critical issue in almost every aspect of human society, including the health sector. This study evaluated the preparedness, strengths and weaknesses associated with accreditation of the Surgery Department of the Rivers State University Teaching Hospital for the training programs of the West African College of Surgeons. Methods: A prospective observational study was carried out among team leads of the accreditation sub-committees in the year 2024, using a proforma. Data was presented as percentages and tables. Results: There were multi-level accreditation committees and sub-committees that worked for the success of the accreditation. The requirements and scores improved with consecutive phase of evaluation. Surgical and anaesthesia manpower, radiologic services, operating theatre, intensive care unit, physiotherapy services, resident doctors’ welfare and utilities all had 80% and above. Consultants’ welfare met 50% requirement, while others were between 50%-80%. Conclusions: Manpower, facilities, utilities and environment of practice, some surgical support services and residents’ welfare, were areas of strength. Improvement in consultants’ welfare and software programs that drive residency training is highly recommended in preparation for subsequent accreditations visits.